PENGARUH KARAKTERISTIK INDIVIDU, MOTIVASI KERJA, DAN MANAJEMEN PENGETAHUAN TERHADAP KINERJA PEGAWAI DINAS PEMBERDAYAAN MASYARAKAT DAN DESA PROVINSI SULAWESI TENGGARA - Doly Rinjaya; Nurwati Nurwati; Nasrul Nasrul; Endro Sukotjo; Alida Palilati; Riski Amalia Madi (Pascasarjana Universitas Halu Oleo, 2020)
This study aims to determine and analyze the effect of individual characteristics, work motivation and knowledge management on employee performance at the Office of Community Empowerment and Villages of Southeast Sulawesi Province. This research approach is quantitative. The population in this study was 77 employees of the Office of Community Empowerment and Village of Southeast Sulawesi Province, and all of them were made respondents. The data collected was analyzed using Partial Least Square (PLS) using the SmartPLS M3 2 program package.The analysis shows that individual characteristics have a positive and significant effect on performance, meaning that the better the individual characteristics of employees will improve performance. Work motivation has a positive and significant effect on performance, which shows that the better employee motivation will improve performance. Knowledge management has a positive and significant effect on performance, which shows that the better management of existing knowledge will improve employee performance.